Inovasi Semprot Anti Nyamuk Ramah Lingkungan Berbasis Ekstrak Serai (Cymbopogon citratus) di Desa Koto Tuo Barat - Hemalia Riyani; Andryani Andryani; Adinda Dwi Nur Junaidi; Arini Attahira; Azwar Hidayat; Dini Karnia; Jelita br. Tamba; Nasywa Aulisa Salsabila; Novri Naldino; Marcel Situmorang (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Riau, 2025)
Mosquitoes are dangerous diseases such as dengue fever and malaria that often cause public health problems. To overcome this, training activities were carried out on making anti-mosquito sprays made from natural ingredients and lemongrass extract (cymbopogon citratus) containing active mosquito repellent compounds. This socialization was carried out in Koto Tuo Barat Village, Kampar Regency, on October 1, 2025. Aimed at increasing the knowledge and skills of residents in processing natural materials into safe, effective and environmentally friendly products. The results of this activity showed high participation from the community and the ability to make sprays independently. This innovation is not only beneficial for environmental health but also opens up economic opportunities through the sustainable utilization of local potential.